The lonely pony - Hawkins, Sarah (London : Scholastic, 2014)
Mia's mother is a groom at an RSPCA centre so she's used to looking after ponies. But when Polly arrives at the centre, underweight and frightened, Mia knows that this pony is going to need a lot of care and attention. At first Polly is too scared to go near humans, but Mia and her mother spend weeks gently nursing her back to health. With Mia's help, Polly will learn to trust again. An exciting, inspiring story based on a real-life animal rescue. With illustrations throughout and lots of facts about ponies and the RSPCA.
M
b
b